Feasibility of a new helical blade structure for a PV integrated wind turbine in a heat-driven swirling wind field. (15th October 2019) - He, Yuanping; Zhang, Mingxu; Li, Weijun; Su, Junwei; Kase, Kiwamu; Yu, Chuck Wah; Gu, Zhaolin
Abstract: A controllable heat-driven swirling wind turbine system was integrated with a photovoltaics (PV) system for energy generation in a heat-collecting shed. This is a brand-new type of a wind energy generation system; and a helical three-blade structure in a vertical axis was introduced. The stationary pre-rotation vanes have a variable diameter and a helical twist angle of 225°. A numerical simulation was conducted to investigate the feasibility of a wind turbine blade structure for efficient energy output for industrial application. The computational fluid dynamics (CFD) tool OpenFOAM was used to simulate the operating conditions of the wind turbine. The findings illustrated the efficacy of the new system. The new helical blade structure is efficient for wind energy output of the turbine in a swirling wind field. The simulation under different heat source temperatures illustrated that an increase in heat source temperature could increase the output efficiency of the wind turbine energy system. The increment in output efficiency could be up to 19.07% when the temperature rises from 40 K to 80 K. The PV-swirling wind integrated system was shown to be more economical than a single solar photovoltaic system because its investment payoff period could be shortened by 2 years. Highlights: A PV-integrated wind turbine system in a swirling wind field is proposed. Helical blade turbine is proven feasible for swirling wind energy output. Structural parameters and operating modes are optimized using CFD simulation.